1991
DOI: 10.1128/aac.35.10.2135
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Staphylococcus species and subspecies to fleroxacin

Abstract: Twenty-four Staphylococcus species or subspecies were examined for their susceptibilities to the fluoroquinolone fleroxacin (Ro 23-6240) by disk diffusion (5-jig disk) and by agar dilution for the determination of MICs.Resistant strains were further tested for their susceptibilities to oxacillin and the fluoroquinolone ciprofloxacin. Reference strains of the novobiocin-resistant species (Staphylococcus saprophyticus, Staphylococcus cohnii, Staphylococcus xylosus, Staphylococcus arlettae, and Staphylococcus gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 7 publications
1
13
0
1
Order By: Relevance
“…Overall, the concentrations of fleroxacin achieved in human tissue appear quite promising compared with the sensitivity of a wide range of microorganisms to fleroxacin. Thus, while the MICs for 90% of strains tested (MIC90s) for virtually all members of the family Enterobacteriaceae are <0.5 ,g/ml (with the MIC90 for Serratia marcescens of <1 ,ug/ml and that for Providencia species of <2 ,ug/ml), peak concentration of fleroxacin are well over 5 ,ug/g in all extracranial tissues after a standard 400-mg dose, with a sustained concentration above the MIC90 in virtually all tissues for at least 6 to 8 h. In addition, the MIC90s for such organisms as Acinetobacter anitratus (4 ,ug/ml) and methicillin-sensitive and methicillin-resistant S. aureus (1 p,g/ml) are also within reach of the levels of fleroxacin achieved in tissues (2,6). Thus, this study suggests that fleroxacin should be particularly useful against urinary tract, gastrointestinal, hepatobiliary, skeletal, and pulmonary infections and that it has promise for the treatment of infections due to these organisms at other sites such as the prostate, uterus, and muscle.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Overall, the concentrations of fleroxacin achieved in human tissue appear quite promising compared with the sensitivity of a wide range of microorganisms to fleroxacin. Thus, while the MICs for 90% of strains tested (MIC90s) for virtually all members of the family Enterobacteriaceae are <0.5 ,g/ml (with the MIC90 for Serratia marcescens of <1 ,ug/ml and that for Providencia species of <2 ,ug/ml), peak concentration of fleroxacin are well over 5 ,ug/g in all extracranial tissues after a standard 400-mg dose, with a sustained concentration above the MIC90 in virtually all tissues for at least 6 to 8 h. In addition, the MIC90s for such organisms as Acinetobacter anitratus (4 ,ug/ml) and methicillin-sensitive and methicillin-resistant S. aureus (1 p,g/ml) are also within reach of the levels of fleroxacin achieved in tissues (2,6). Thus, this study suggests that fleroxacin should be particularly useful against urinary tract, gastrointestinal, hepatobiliary, skeletal, and pulmonary infections and that it has promise for the treatment of infections due to these organisms at other sites such as the prostate, uterus, and muscle.…”
Section: Discussionmentioning
confidence: 80%
“…Both in vitro and in animal models, fleroxacin's anti-gram-negative-bacterium activity has been shown to be comparable to that of the earlier fluoroquinolones (norfloxacin, pefloxacin, ciprofloxacin, and ofloxacin) (1,2,7,11,13,19,29,36,37,40). In addition, however, studies in endocarditis models, as well as in vitro, have shown that fleroxacin has significant activity against both methicillin-susceptible and -resistant Staphylococcus aureus (1,6,25,28).…”
mentioning
confidence: 98%
“…However, with the increased use of this group of antibiotics, particularly ciprofloxacin, there have been reports of resistant CNS (21,23,72,101,181). Studies have indicated that resistance to one quinolone may predispose the isolate to become resistant to other quinolones (21,257,296,319).…”
Section: Conventional Methodsmentioning
confidence: 99%
“…However, with the increased use of this group of antibiotics, particularly ciprofloxacin, there have been reports of resistant CNS (21,23,72,101,181). Studies have indicated that resistance to one quinolone may predispose the isolate to become resistant to other quinolones (21,257,296,319). Some investigators have tried to induce resistance to the quinolones by serial passages in the presence of the antibiotics (23,224,284 (88).…”
Section: Conventional Methodsmentioning
confidence: 99%
See 1 more Smart Citation